Voice Assistants in Private Homes: Media, Data and Language in Interaction and Discourse (Media in Action, 2025)
Voice Assistants such as Amazon's Alexa populate private homes as well as smartphones, TVs and cars. While suggesting easy living with smart devices, these assistants are criticized as the next step of corporate and state surveillance of the private home, or as harbingers of new and simplified linguistic practices. The contributors to this volume focus on the transformation and persistence of everyday linguistic, media and data practices under platformized conditions and new interfaces. This collection thus brings together perspectives from media sociology, media studies, media linguistics and domestication research.